2021
DOI: 10.1364/oe.443666
|View full text |Cite
|
Sign up to set email alerts
|

Low pump power coherent supercontinuum generation in heavy metal oxide solid-core photonic crystal fibers infiltrated with carbon tetrachloride covering 930–2500 nm

Abstract: All-normal dispersion supercontinuum (ANDi SC) generation in a lead-bismuth-gallate glass solid-core photonic crystal fiber (PCF) with cladding air-holes infiltrated with carbon tetrachloride (CCl4) is experimentally investigated and numerically verified. The liquid infiltration results in additional degrees of freedom that are complimentary to conventional dispersion engineering techniques and that allow the design of soft-glass ANDi fibers with an exceptionally flat near-zero dispersion profile. The unique c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…[119] The absolute dispersion values varied between -150 and -5 ps/nm/km for the 1-2 μm spectral range. In a few other experiments, Hoang, Van Le et al also presented several HCF designs infiltrated with CCl 4 showing flat normal dispersion in a broad spectral range (i.e., 0.8-1.7 μm [120] and all-normal up to 2.5 μm [121] ).…”
Section: Hollow-core Fibers With Liquid-corementioning
confidence: 96%
See 2 more Smart Citations
“…[119] The absolute dispersion values varied between -150 and -5 ps/nm/km for the 1-2 μm spectral range. In a few other experiments, Hoang, Van Le et al also presented several HCF designs infiltrated with CCl 4 showing flat normal dispersion in a broad spectral range (i.e., 0.8-1.7 μm [120] and all-normal up to 2.5 μm [121] ).…”
Section: Hollow-core Fibers With Liquid-corementioning
confidence: 96%
“…In a few other experiments, Hoang, Van Le et al. also presented several HCF designs infiltrated with CCl 4 showing flat normal dispersion in a broad spectral range (i.e., 0.8–1.7 μ$\umu$m [ 120 ] and all‐normal up to 2.5 μ$\umu$m [ 121 ] ).…”
Section: Commonly Used Materials Systems and Fiber Designsmentioning
confidence: 99%
See 1 more Smart Citation
“…Junaid et al filled the microstructure fiber with CS 2 and used 30 fs and 90 fs pulse pumps respectively to obtain a SC spectrum of 1-2.2 µm experimentally [28]. Le et al reported the discovery of high-quality, high-coherence SC covering 0.9-2.5 µm in lead-bismuth-gallate (PBG) glass PCF infiltrated with CCl 4 [29]. Alternatively, using tapered fibers is another method to enhance spectral broadening to the MIR region owing to their enhanced dispersion or nonlinearity design freedom [30].…”
Section: Introductionmentioning
confidence: 99%
“…High nonlinear PCF is an excellent nonlinear optical medium to generate supercontinuum [17] . In recent years, SCG in liquid-core bers has attracted more and more attention due to the superior performance of some inorganic solvents [18,19] , such as carbon disul de (CS 2 ) [20] , carbon tetrachloride (CCl 4 ) [21] , tetrachloroethylene (C 2 Cl 4 ) [22] , toluene [23] , nitrobenzene [24] and so on. These inorganic solvents have good transmission properties and large nonlinear coe cients in the visible to near-infrared spectral region, and also exhibit strong non-instantaneous nonlinearity due to the slow molecular motion of liquid [25] , which is one of the ideal nonlinear mediums for SCG [26] .…”
Section: Introductionmentioning
confidence: 99%